Policy uncertainty, lender of last resort and the real economy - Martina Jasova; Caterina Mendicino; Dominik Supera (European Central Bank (ECB), 2021)
We show that a reduction in lender of last resort (LOLR) policy uncertainty posi-tively affects bank lending and propagates to investment and employment. We exploita unique policy that reduced uncertainty regarding the availability of future LOLRfunding for banks as a quasi-natural experiment. Using micro-level data on banks, firms and loans in Portugal, we generate cross-sectional variation in banks' exposureto uncertainty and find that the size of thehaircut subsidy - the gap between privatemarket and central bank security valuations - plays a key role in the propagation ofthe shock to lending and the real economy.
Keywords: E44; E52; E58; G21; G32; 330; Bank Credit; Haircut Subsidy; Central Bank Liquidity; Policy Uncertainty; Firm-level Employment and Investment